Pengaruh Iklim Organisasi Dan Pengembangan Karir Terhadap Semangat Kerja Karyawan Pada PT. Mahakam Energi Berkah - Johansyah Johansyah; Muhammad Habibi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2021)
Abstract: The purpose of this study was to determine the effect of organizational climate variables and career development on employee work spirit simultaneously and partially. In addition, to determine the most dominant variable affecting employee work spirit at PT. Mahakam Energy Blessing in Tenggarong Seberang. The responden in this study were all production employees at PT. The Mahakam of Blessing Energy numbered 93 people. The analytical tool used is qualitative analysis with multiple regression models. Based on the simultaneous test table, it can be concluded that the variable organizational climate and career development simultaneously affect employee morale. Organizational climate and career development variables have a partial effect on employee morale. From the two partial correlation test results, it can be seen that the value of the organizational climate variable is the largest compared to the career development variable, so that the organizational climate variable is the most dominant variable affecting work morale. Keywords: Organizational Climate, Career Development, Work Spirit